Parasites driving host diversity: Incidence of disease correlated with Daphnia clonal turnover*. (5th January 2018) - Turko, Patrick; Tellenbach, Christoph; Keller, Esther; Tardent, Nadine; Keller, Barbara; Spaak, Piet; Wolinska, Justyna
Abstract: According to the Red Queen hypothesis, clonal diversity in asexual populations could be maintained by negative frequency‐dependant selection by coevolving parasites. If common clones are selected against and rare clones gain a concomitant advantage, we expect that clonal turnover should be faster during parasite epidemics than between them. We tested this hypothesis exploring field data of the Daphnia – Caullerya host–parasite system. The clonal make‐up and turnover of the Daphnia host population was tracked with high temporal resolution from 1998 until 2013, using first allozyme and later microsatellite markers. Significant differences in the clonal composition between random and infected subsamples of Daphnia populations were detected on six of seven tested occasions, confirming genetic specificity of the host–parasite interaction in this system. We used time series analysis to compare the rates of host clonal turnover to the incidence of parasitism, and found that Caullerya prevalence was significantly associated with microsatellite‐based clonal turnover. As alternate hypotheses, we further tested whether turnover was related to a variety of biotic, abiotic, and host demographic parameters. Other significant correlates of turnover were cyanobacterial biomass and (weakly) temperature. Overall, parasitism seems to be a strong driver of host clonal turnover, in support of the Red Queen hypothesis.